Compatibilidade de conjuntos de criterios e indicadores para avaliar a sustentabilidade do manejo florestal na Amazonia Brasileira - Pokorny, B.; Adams, M. (Center for International Forestry Research, 2003)
Criteria and indicators (C&I) are tools to define, communicate and evaluate the sustainability of forest management. Since the Rio summit in 1992, numerous initiatives developed a various C&I sets as multifunctional tools to be applied for monitoring, auditing, science and decisions makers. The existing diversity of C&I sets is a cause for uncertainty and confusion, and thereby diminishes the acceptance and efficiency of the tool. With the initial aim to better understand this diversity, this study compared the content and the quality of five C&I sets relevant for the Brazilian Amazon (CIFOR, MCA, FSC, ITTO e Tarapoto). In addtion some principle actors of forest management in the region were interviewed. The study revealed differnt thematic foci of the analysed C&I sets. There was also detected signficant deficiencies in relation to validity, specificity and practicability of the indicatores. Most of the C&I sets only present a list for collecting information, but not the norms to interpret the collected data. In order to increase objectivity and transparency of C&I based assessment it is necessary to develop less complex and more practicable C&I sets. C&I must reflect more clearly and unambiguously what is actually assessed by defining verifiers and practicable methods for their assessment. It is important to provide more adequate tools and intensive training to people dealing with the development of C&I.